Public Policies for Climate Change Mitigation in Indonesia - Joko Tri Brata; Fadhlih Toparakkasi (Universitas Negeri Makassar, 2023)
This article examines public policies aimed at addressing climate change in Indonesia. As one of the world's most vulnerable countries to the impacts of climate change, Indonesia faces significant challenges in mitigating its effects and promoting sustainability. The study analyzes key public policies implemented in Indonesia to combat climate change, explores their effectiveness, and identifies areas for improvement. A mixed-method approach is employed, incorporating quantitative analysis of policy outcomes and qualitative examination of policy instruments and stakeholder perspectives. The findings highlight the importance of integrated and multi-sectoral approaches, stakeholder engagement, and international cooperation in addressing climate change. The article contributes to the existing literature on climate change policy by providing insights into the Indonesian context and offering recommendations for enhancing policy effectiveness.